Econometric methods in the analysis of duary total production costs - Cobo, Ferm?n Ra?l; Torres, Verena; Machado, Yenia; Fraga, M. (Cuban Journal of Agricultural Science, 2011)
In order to apply the linear regression technique in the analysis of milk production costs and obtain their division in fixed and variable components, a database was prepared with information from the two milk production units of the Institute of Animal Science. Data were collected including the last five years. In order to estimate the total costs, the method of least squares was used permitting to obtain the estimated values of the fixed and variable costs. Models were revealed accounting for 88.9 % and 60.8 % of the performance of the total costs in both units. In the two models, there was statistically significant ratio (P < 0.01) for the 99 % confidence values, according to the tables of the regression analysis. The separation of the costs was attained according to their elements from the econometric techniques that facilitate the interpretation of the information. The need for particularizing and deepening into the forming elements of the total production cost was proved in a way that correct decision making could be guaranteed in a way that production costs can bve reduced or the volume of the income sources can be increased. Key words: fixed costs, variable costs, linear regression.